Therapeutic exercise : foundations and techniques - Kisner, Carolyn; Borstad, John; Colby, Lynn Allen (Philadelphia, PA : F.A. Davis Company, 2023)
'The authors and contributors of this book have continually sought to incorporate current trends and research to support the foundational concepts of therapeutic exercise on which the student can learn, and the practitioner can grow in their expertise of treating patients. In addition to the extensive and thorough revisions of content, the Focus on Evidence and Clinical Tips features, as well as links to video demonstrations of key interventions, are again highlighted in this edition. Whenever applicable, up to date Clinical Practice Guidelines (CPGs) are included within the Focus on Evidence sections. As with previous editions, it is our hope that this updated text will provide a resource for learning and professional growth for the students and health-care practitioners who utilize therapeutic exercise'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Exercise Therapy; Physical Therapy Modalities